Post-Marriage Guidance System in the Berkah Program and Implications for Reducing Divorce Rates in Kua, Banyuwangi District - Roihan Firdaus Nuris; Kun Wazis; Martoyo (Syntax Corporation Indonesia, 2023)
The recapitulation of the divorce rate in Banyuwangi District in recent years shows a significant trend, with the number of cases being quite high. In an effort to reduce the divorce rate, the government has initiated the Blessing Program. However, this research found that the program had not achieved overall effectiveness. The concept of the Berkah program is considered to be in accordance with the legal structure, although there are several obstacles in coordinating with sub-districts and determining the marriage age below 10 years. On the other hand, program participants showed enthusiasm and good understanding of the program objectives. The implementation of the Berkah program is generally in line with the theory and guidelines of the Director General of BIMAS Islam, although there are difficulties in coordinating with sub-districts and in selecting places and participant criteria. The impact of the Berkah program includes a significant reduction in the divorce rate, as well as promoting cooperation between the KUA and sub-districts and clarifying the rights and obligations of program participants.